Bagon Village Waste Management Innovation Through Optimizing the Role of the Waste Bank - Nur Andita Prasetyo; Suhesti Yulfiani; Mayang Luthfiah Noviana; Ewin Eka Sofia Wulandari; Ahmad Nawawi (Medikun Publisher, 2024)
Waste management is still a complex matter, and of these problems there are many program innovations to deal with waste management problems. The program innovation for dealing with waste came from KKN-K students in group 023 who designed work programs that were in line with environmental problems in Bagon Village, namely the lack of handling of waste problems. The lack of waste handling in Bagon Village is proven through the results of a survey directly to the community. The survey results found that most of the people of Bagon Village still littered. The